Biodiesel reactor optimization using combined CFD-Taguchi method - Adeyemi, Nabeel A.; Mohiuddin, A. K. M.; Jameel, Ahmed Tariq (2010)
Biodiesel is currently produced from food and non food oil sources through transesterification. The process is significantly constrained by reaction kinetics and mass transfer. In the present article, the transesterification of waste cooking oil (WCO) at different reaction parameters is carried out to investigate the effect of reactor configuration on yield. The Taguchi design, with temperature, impeller speed and bottom distance as process variables at 3 levels, is used to plan, analyze and optimize the process. Optimum yield was predicted for 60°C, 600 rpm and 25mm temperature. Statistical analysis reveals the impeller distance as most significant of the variables to affect yield and a 2D computational fluid dynamics (CFD) simulation of the mixing correlated an impeller bottom clearance of 25mm to the highest yield.